Disentangling metabolic and neurovascular timescales supporting cognitive processes - Francesca Saviola; Stefano Tambalo; Laura Beghini; Asia Ferrari; Barbara Cassone; Dimitri Van De Ville; Jorge Jovicich (Proceedings of the National Academy of Sciences, 2025)
The balance between neural excitation and inhibition (EIB), governed by glutamatergic and GABAergic neurotransmission, is an essential mechanism supporting cognitive processes. Yet, little is understood about how EIB shifts with engaging cognitive load and its impact on functional connectivity dynamics. Here, we combined time-resolved functional magnetic resonance spectroscopy and magnetic resonance imaging to investigate temporal profiles of the reciprocal modulation between EIB and functional network dynamics during working memory tasks in healthy subjects. We quantified EIB kinetics by measuring excitatory (Glx) and inhibitory (GABA+) levels and assessed their temporal coupling with dynamic functional connectivity states, revealing a dependence that scales with cognitive load. Notably, we found that as cognitive challenges intensify, brain networks transition toward more specialized and enduring connectivity configurations, accompanied by imbalances that favor excitation, changes that may impact cognitive adaptability. Fluctuations in EIB and functional connectivity occurred on comparable timescales and were both associated with individual differences in cognitive performance. Importantly, this experimental approach demonstrates a close synergy between EIB kinetics, brain network dynamics, and cognitive performance, defining the groundwork for exploring healthy and aberrant cognitive states.